The Islamization Of Knowledge - Andi Holilulloh; Fouad Larhzizer (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2020)
This paper will analyse the discourse of Islamic reconciliation and modern science experienced a debate between Nidhal Guessoum and Ismail Al-Faruqi. Guessoum's thought bridges religion with science in using of quantum approach method to integrate both of them. The research results show that quantum approach itself is based on three principles: the principle of non-contradiction, the principle of multi-layered interpretation, the principle of falsification-theistic. Ismail al-Faruqi has a brilliant idea in finding solutions to the problems of muslims’ life. The idea is inseparable from the concept of tauhid as the essence of Islam. his idea of ​​the Islamization of science as knowledge meant the Islamization of modern science by carrying out scientific activities such as elimination, change, reinterpretation and adjustment of its components